What would you like to do?
It depends what x is...
x2+10x+1 = -12+2x x2+10x-2x+1+12 = 0 x2+8x+13 = 0 Solving by using the quadratic equation formula: x = - 4 - or + the square root of 3
x2+10x+1 = -12+2x x2+8x+13 = 0 The solution: x = -4 + the square root of 3 or x = -4 - the square root of 3
The 'solution' is the number that 'r' must be in order to make the statement true. Here's how to find it: 6r - 1 + 6r = 11 Add 1 to each side: 6r + 6r = 12 Clean… up the left side: 12r = 12 Divide each side by 12: r = 1
a= 2, b = 3 (or vice-versa)
8x - 19 = 3x + 1 5x -19 = 1 5x = 20 x = 4
Thanks to the browser, it is not possible to tell what the inequalities are.
x2 + x - 1 = 0 Using the quadratic formula this gives us: x = (-1 + or - (-12 - (4 * 1 * -1))1/2) / 2 * 1 x = (-1 + or - (1 - - 4)1/2) / 2 x = (-1 + or - 51/2) / 2 x = 0.618 a…nd -1.618 (Both given to 3 decimal places only) Note: x1/2 means the square root of x.
Yes, but so is everything else.
The value of c is 6
4x+1 -3 = 26 first, +1 and -3 = -2 Move the -2 to the other side of the = sign, and it becomes +2. +26 +(+2) = 28 Now we have 4x = 28 Divide both sides by 4 and you have 4x/4… = 28/4 Perform that division and the answer is x = 7
The sequence is poorly defined. 1+3+5 appears to be a sequence of odd numbers. However, that cannot end in 100: it can attain the values of 99 or 101. Obviously the answer wi…ll depend on which one of these is the final number. An alternative is that the sequence is not that of odd numbers but some other sequence: for example, t(n) = (29n 3 - 174n 2 + 399n - 214)/40 which, for n = 1, 2, 3, generates the sequence 1, 3, 5, 11.35, 26.4, 54.5, 100 whose sum is 201
There can be no solution set because there is no equation nor an inequality - only an expression. There can be no solution set because there is no equation nor an inequality… - only an expression. There can be no solution set because there is no equation nor an inequality - only an expression. There can be no solution set because there is no equation nor an inequality - only an expression.
If you mean: y = 3x+2 then (-1, -1) will satisfy the straight line equation